An Exploratory study of outsourcing in the Kenyan manufacturing industry - Ouma, Albert (Strathmore University, 2010)
The dissertation is a qualitative exploratory research about outsourcing in the Kenyan beverage manufacturing industry. Outsourcing is a filly-fledged strategic business trend around the world. The potential for outsourcing has moved from peripheral activities such as cleaning and catering to critical activities such as product design and manufacturing. In today’s business environment companies are driven to perform few functions in-house and get the rest from other outside sources through aggressive outsourcing. The goal of companies that aggressively outsource most functions is to enhance competitiveness by achieving a higher return on assets through less capital commitment and increasing the ability to quickly adjust to a changing environment through less commitment to in-house resources. The overall objective of the study was to advance the understanding of the current status, scope and the implications of the organizations’ reliance on outsourcing decisions in the beverage manufacturing industry in Kenya. The study developed a conceptual research framework and examined the main variables within it. Four research questions that related to the objectives of the study were identified. Comprehensive literature review was constructed. The research study used a survey questionnaire and face to face interviews in which a number of questions were asked to the respondents who had a direct influence on outsourcing decisions in the beverage manufacturing industries in Kenya. Four propositions were developed and justified from the literature review. Conclusions and implications for rc’search study were completed and the recommendations for further study made. The circular research process was completed and this indicated that outsourcing is a Strategic business process that currently involves outsourcing of peripheral functions with an advancing (rend towards outsourcing core functions.
Partial fulfillment for award of the degree of Master of Business Administration
Keywords: Contracting Out--Kenya; Business Logistics--Contracting Out; Production Management